2019
DOI: 10.1002/jmri.26614
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms for Cardiovascular Magnetic Resonance Measurements in the Pediatric Age Group: To Define the Normal and the Expected Abnormal Values in Corrected/Palliated Congenital Heart Disease: A Systematic Review

Abstract: Our purpose is to provide an overview and to systematically review the strengths and limitations of studies on pediatric and adolescent normal values for cardiovascular MRI parameters. A literature search was performed within the National Library of Medicine using the following keywords: normal, reference values, cardiovascular magnetic resonance imaging, and children/pediatric. Eleven published studies evaluating cardiovascular MRI measurements in normal children were included in the present analysis. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
(390 reference statements)
0
3
0
Order By: Relevance
“…We report maximum, minimum, and mean diameters as well as the cross-sectional areas for these structures. Normative values in children exist for echo, CMR, and non ECG -gated CTA but are lacking for ECG-gated-CTA [35][36][37] . Few non-ECG-gated CTA studies reported normative measurements so far.…”
Section: Discussionmentioning
confidence: 99%
“…We report maximum, minimum, and mean diameters as well as the cross-sectional areas for these structures. Normative values in children exist for echo, CMR, and non ECG -gated CTA but are lacking for ECG-gated-CTA [35][36][37] . Few non-ECG-gated CTA studies reported normative measurements so far.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring cardiac structures with a precise approach all these data were mainly based on paediatric populations (21,22). The calculation of Z-scores has been widely used to normalize paediatric cardiac parameters in two-dimensional echocardiography, three-dimensional echocardiography and even cardiovascular magnetic resonance (23,24). However, not all cardiac parameters show good coefficients of determination for computing Z-scores, such as echocardiographic strain (ε) (25).…”
Section: Left Ventricular Size and Normative Datamentioning
confidence: 99%
“…However, to interpret quantitative CMR results, disease-specific RV reference values are desirable that can be used for comparison especially in patients with no serial follow-up data [7] , [8] . It was therefore the goal of this study to create CMR reference values for RV volumetric variables in patients with HLHS from early childhood to adulthood.…”
Section: Introductionmentioning
confidence: 99%